2018
DOI: 10.18632/oncotarget.25247
|View full text |Cite
|
Sign up to set email alerts
|

Identification of radiation responsive genes and transcriptome profiling via complete RNA sequencing in a stable radioresistant U87 glioblastoma model

Abstract: The absence of major progress in the treatment of glioblastoma (GBM) is partly attributable to our poor understanding of both GBM tumor biology and the acquirement of treatment resistance in recurrent GBMs. Recurrent GBMs are characterized by their resistance to radiation. In this study, we used an established stable U87 radioresistant GBM model and total RNA sequencing to shed light on global mRNA expression changes following irradiation. We identified many genes, the expressions of which were altered in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…et al, 2016). In a radioresistant GB model, the total RNA was sequenced and it was found that there was a positive regulation of macrophage chemotaxis following radiation (Doan et al, 2018). Also, in a murine glioma model, an increase in SDF-1a at the tumor invasion front after radiotherapy was correlated with the recruitment of TAMs and radioresistance (Wang et al, 2013).…”
Section: Tams and Radiotherapymentioning
confidence: 98%
“…et al, 2016). In a radioresistant GB model, the total RNA was sequenced and it was found that there was a positive regulation of macrophage chemotaxis following radiation (Doan et al, 2018). Also, in a murine glioma model, an increase in SDF-1a at the tumor invasion front after radiotherapy was correlated with the recruitment of TAMs and radioresistance (Wang et al, 2013).…”
Section: Tams and Radiotherapymentioning
confidence: 98%
“…A radiosensitivity signature, comprising of DNA repair and cell cycle-related genes (identified in breast cancer cell lines and validated in an independent patient dataset) was successful in predicting local recurrence [10]. Another study reported an increase in expression of genes involved in epithelial-to-mesenchymal (EMT) transition, angiogenesis, and proliferation in a highly radio-resistant tumor, glioblastoma [11]. Also, a study of genomic alterations in breast cancer patients revealed an association of phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) mutation with loco-regional recurrence in case of breast cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the molecular and genomic changes post-radiation in pediatric GBM have not been well examined. We have recently identified many radiation-responsive genes in adult radioresistant GBM cells that explain the radioresistance and increased malignant features of recurrent GBM [ 4 ]. However, adult and pediatric GBMs are distinct from each other at both molecular and genetic levels [ 2 ].…”
Section: Introductionmentioning
confidence: 99%